[De] constructing South Africa's Jacob Zuma led ANC: An Afrocentric perspective. Issue 4 (18th July 2018) - Shai, Kgothatso B.; Nyawasha, Tawanda S.; Ndaguba, Emeka A.
Abstract : Based on the Afrocentric perspective, the central thesis of this paper is that if the African National Congress (ANC) is to evade the wrath of coalition politics in the near future (year 2019); it needs more than its traditional support base and appeals for liberation rhetoric. Like other liberation movements cum ruling political parties in Southern Africa, indications are that ANC cannot save itself from the brutality of competitive politics and electoral democracy. While the ANC is based in South Africa, it remains the political heritage of all Africans, and as such, it can only survive further degeneration through the collective efforts of pan‐Africanists in the country and across the corners of the continent. The fact that President Jacob Zuma led ANC did not have a safe liberalised space for counsel by non‐active members has rendered any possible renewal through the support of all Africans a pipe dream. Although the renewal of the ANC may be necessary for the sake of preserving liberation heritage in South Africa and Africa at large, it is concluded that the weakening of dominant political parties such as the ANC is a necessary ingredient for healthy and functioning democracies.